A clinical trial comparing antimicrobial efficacy of “essential oil of Ocimum sanctum” with triple antibiotic paste as an intracanal medicament in primary molars - Pratibha Ahirwar; N D Shashikiran; Ravi Kadur Sundarraj; Shilpy Singhla; Ruchi Ahuja Thakur; Satish Maran (Journal of Indian Society of Pedodontics and Preventive Dentistry, 2018)
Objectives: To evaluate the aerobic and anaerobic antimicrobial efficacy of Ocimum Sanctum (Tulsi) essential oil and compare it with that of triple antibiotic paste (TAP) by collecting microbiological samples from the root canals of primary molars. Study Design: Forty children were selected for the study and were randomly divided into two groups of twenty each, namely, TAP group and O. sanctum group (basil). Six intracanal samples were collected for every patient, comprising of two each after access opening, irrigation and after 3 days of intracanal medicament placement. These samples were cultured in aerobic and anaerobic environment and later colony-forming units (CFUs) were counted and intragroup as well as intergroup comparison was done. Results: Analysis of the results showed that there was a statistically significant reduction in CFUs after using essential oil of O. sanctum as an intracanal medicament. Saline use also leads to a statistically significant reduction in CFUs irrespective of the intracanal medicament used. TAP showed better antibiotic properties in comparison with that of O. sanctum. Conclusion: Antibiotic use is often associated with the adverse effects and development of resistance due to injudicious use. O. sanctum can be used in cases of long-standing infection owing to its antimicrobial efficacy and anti-inflammatory potential as an intracanal medicament in primary teeth.